The Philippines: Beyond Resilience: Protecting the Rights of Internally Displaced Persons in Dulag, Leyte in the wake of Super Typhoon Haiyan - Quan, Ryan Jeremiah D (Archīum Ateneo, 2020)
This chapter focuses on the immediate period leading up to; during; and shortly after the typhoon. It focuses on the municipality of Dulag in the province of Leyte. Displacement in the context of disasters and climate change; no matter the duration; affects human rights. As such; disaster-prone countries like the Philippines must take measures to protect the rights of affected populations. The chapter describes and understands the experiences of individuals and local authorities before; during; and after Haiyan; and assesses if the existing laws; policies; guidelines; and mechanisms were sufficient to effectively address the needs and concerns of the members of communities affected by the typhoon. The National Disaster Risk Reduction and Management Plan 2011–2028 operationalises the National Disaster Risk Reduction and Management Framework to achieve the country’s Disaster Risk and Reduction Management vision – ‘safer; adaptive and disaster resilient Filipino communities towards sustainable development.’.